The salience of fakeness: Experimental evidence on readers’ distinction between mainstream media content and altered news stories - Maniou, Theodora A.; Papa, Venetia; Bantimaroudis, Philemon (My University, 2020)
This experiment was designed to explore people’s critical, differentiating capacity between actual news and content that looks like news. Four groups of post-millennials read four versions of a news story. While the first condition included a real news story derived from a mainstream medium, the other three conditions tested three attributes of fakeness, namely an exaggerated, satirical, and popularised frame of disinformation. Although readers differentiated between satire and the actual news story, no significant differences were observed between exaggerated and simplified versions of news and the actual news story. Additional intervening variables were scrutinized, showing a connection between the salience of a story and its perceptions of fakeness.
Keywords: Salience; Fake news; Agenda-setting; Disinformation; Post-millennials